Sex hormones influence the intestinal microbiota composition in mice - Wu, Yi; Peng, Xinxin; Li, Xiaoya; Li, Dandan; Tan, Zhoujin; Yu, Rong (Frontiers in Microbiology, 2022)
Sex hormone secretion difference is one of the main reasons for sexually dimorphic traits in animals, which affects the dimorphism of the intestinal microbiota; however, their interaction is still unknown. Intestinal mucosa-associated microbiota (MAM) and intestinal luminal content microbiota (LM) belong to two different habitats according to the difference in interactions between bacteria and host intestinal epithelium/nutrients. To clarify the sexually dimorphic characteristics of MAM and LM and their correlation with sex hormones, 12 specific pathogen-free (SPF) Kunming mice from the same nest were fed separately according to sex. After 8 weeks, samples from the male intestinal mucosa group (MM group), the female intestinal mucosa group (FM group), the male intestinal content group (MC group), and the female intestinal content group (FC group) were collected and then, the next-generation sequencing of 16S ribosomal ribonucleic acid (rRNA) gene was performed. Our results showed that the sexual dimorphism of MAM was more obvious than that of LM and the relative abundance of Muribaculaceae, Turicibacter, and Parasutterella was significantly higher in the FM group than in the MM group (p < 0.001, p < 0.05, p < 0.05). Next, we measured the level of serum sex hormones in mice and calculated the correlation coefficient between major bacteria and sex hormones. The results showed that the correlation between MAM and sex hormones was more prominent, and finally, three bacterial genera (Muribaculaceae, Turicibacter, and Parasutterella) were obtained, which could better represent the relationship between sexual dimorphism and sex hormones. The abundance of Parasutterella is positively and negatively correlated with estradiol and testosterone (T), respectively, which may be related to the differences in the metabolism of bile acid and glucose. A decrease in the abundance of Turicibacter is closely related to autism. Our results show that the abundance of Turicibacter is negatively and positively correlated with T and estradiol, respectively, which can provide a hint for the prevalence of male autism. In conclusion, it is proposed in our study that intestinal microbiota is probably the biological basis of physiological and pathological differences due to sex, and intestinal MAM can better represent the sexual dimorphism of mice.